Perubahan-Perubahan Segmental pada Pertumbuhan Anak Perempuan Umur 7-10 Tahun di Yogyakarta - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1980)
ABSTRACT The growth in stature actually consists of segmental growth, because it could be divided into various segments, i. e.: head and neck, trunk, and upper and lower leg. All segments grow independently under their own velocity